Transepidermal water loss and skin conductance as barrier integrity tests - Zhang, Qian (Toxicol In Vitro, 2018)
In vitro skin permeation studies are commonly used in the risk assessment of toxic compound skin exposure. The present study examined the utility of transepidermal water loss (TEWL) and electrical conductance as barrier integrity tests before skin permeation studies in vitro using a large number of skin samples and fentanyl. TEWL and conductance of the skin samples were measured before the permeation experiments in Franz diffusion cells in vitro with a vapometer and low voltage application, respectively. The data were analyzed based on the in vitro permeation results and in vivo skin absorption information from the transdermal fentanyl product labels. The results showed poor correlations between TEWL and electrical conductance for the skin samples. Weak correlations between fentanyl delivery rate (flux × area) and TEWL and skin conductance were observed. For comparison, TEWL and conductance were also examined after skin perturbation with a syringe needle, and both TEWL and conductance values of the skin samples increased after the perturbation. The data suggest that either TEWL of 10 g/m(2)/h or skin conductance of 0.07 mS/cm(2) can be used as exclusion criteria in skin integrity testing to remove skin samples with high permeabilities under the in vitro conditions studied.